Strategi Pemasaran Objek Wisata Taman Doa Bunda Maria Kota Gunungsitoli Kabupaten Nias - Regina Ratna Bawamenewi; Harisan Boni Firmando; Mery Silalahi; Robert J.T. Sitio; Tio Rj Nadeak (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to find out the marketing strategy of the manager of the Mother Mary's Prayer Park tourist attraction and what obstacles the local tourist attraction manager faces in marketing the religious tourist attraction of the Mother Mary's Prayer Park. Mother Mary's Prayer Park is a religious tourism site with Catholic nuances. This type of research is descriptive research with a qualitative approach. The informants in this research are tourism managers, tourism offices, employees and tourist visitors. The data collection methods used are the observation method, interview method, documentation method, data analysis used is data reduction, data display (data presentation), conclusion drawing/verification (conclusion). The results of research on marketing strategies for the religious tourist attraction of Our Lady's Prayer Park include 4 strategies, namely price, promotion, place, product. These four strategies serve as management guidelines for marketing the Mother Mary's Prayer Park tourist attraction. Apart from marketing tourist attractions, there are supporting and inhibiting factors for marketing the religious tourist attraction Our Lady's Prayer Park, Gunungsitoli City.